Telegram - Stolz, George
021-0079-001 F Received at Central Telegraph Office POST OFFICE OVERSEAS TELEGRAM Official particulars, including Office of Origin. 399 PARIS 13827 20 3 1728 = No. 722 To. TEWSON TRADUNIC SOWEST LDN= LOOK FOR PHOTOS OF TOMAS AND LONGUET IN DAILY HERALD AND REYNOLDS NEWS IFTU CONGRESS LONDON = STOLZ = EAB For free repetition of doubtful words telephone NATIONAL 3383. If the telegram was received by telephone DIAL 559. This form and, if possible, the envelope should accompany any written enquiry. 292/946/21/79